Changes in heart rate and blood lactate concentration during karate kata competition - R. Penov; L. Petrov; S. Kolimechkov (IP Iermakov S.S., 2020)
Background and Study Aim : Karate is going to take part in the Olympic games, for the first time in Tokyo 2020. The aim of this study was to analyse the changes in heart rate (HR) and blood lactate concentration of karate practitioners performing different katas in competitive conditions. Material and Methods : This study consisted of five elite male athletes (26.80±5.97 years), members of the Bulgarian national team in Shotokan karate, competing in the kata discipline. The study was conducted in competitive conditions during national competitions, in which three katas were performed by each of the competitors. Capillary blood lactate concentration (La) was determined at rest and after each kata. Heart rate (HR) was registered and physical activity was monitored by using three-dimensional accelerometers. Results: The mean La increased progressively after each following kata: 1.4±0.32 mmol/L at rest, 4.7±1.91 mmol/L after the first, 6.8±2.59 mmol/L after the second, and 7.1±2.35 mmol/L after the third kata. This increase was significant after the second (р<0.05) and third (р<0.01) kata, in comparison with the registered La at rest. The mean HR values reached 179±11.55 bpm during the first, 180±11.63 bpm during the second, and 181.5±15.44 bpm during the third kata. Conclusions: The La appeared to be a more informative parameter than heart rate, and the moderate increase of the La values (4-6 mmol/L) indicated optimal muscle tension and amplitude of moves when performing katas in competitive conditions. Further research is needed to determine the optimal La levels for the performance of different katas.